Leader dismissal or continuity, president longevity, geographic orientation of owners and team performance: Insights from French men's football, 1994-2016 - Nicolas Scelles; Matthieu Llorca (Journal of Risk and Financial Management, 2021)
We investigated the impacts of president longevity and the geographic orientation of owners on team performance and on the effectiveness of dismissing the leader. In addition, we considered their impacts on the effectiveness of not dismissing the leader while the same organisation fires them at another time for a similar performance. We also tested the impact of dismissing the leader or not on performance. We explored the aforementioned risk-taking relationships in the first tier of French men's football over the 1994-2016 period (n = 4918 observations). To do so, we used a counterfactual based on the evolution of the team position over the last three games leading to the leader change and estimate linear regression models with fixed team effects. Our findings show that performance improves either after a leader dismissal or not in the same situation, and both president longevity and the geographic orientation of owners impact the effectiveness of dismissing the leader or not. In particular, global- and local-oriented ownerships have a positive impact on the effectiveness of the decision to dismiss the leader or not compared to national-oriented ownership. Practical implications stem from the research, e.g., how organisations with national-oriented ownership can overcome their competitive disadvantage.
Keywords: 330; French men's football; geographic orientation of owners; leader succession; president longevity; risk-taking; team performance